Perovskite Solar Cells Go Bifacial—Mutual Benefits for Efficiency and Durability - Song, Zhaoning; Li, Chongwen; Chen, Lei; Yan, Yanfa (Advanced materials (Weinheim), 2022)
Bifacial solar cells hold the potential to achieve a higher power output per unit area than conventional monofacial devices without significantly increasing manufacturing costs. However, efficient bifacial designs are challenging to implement in inorganic thin‐film solar cells because of their short carrier lifetimes and high rear surface recombination. The emergence of perovskite photovoltaic (PV) technology creates a golden opportunity to realize efficient bifacial thin‐film solar cells, owing to their outstanding optoelectronic properties and unique features of device physics. More importantly, transparent conducting oxide electrodes can prevent electrode corrosion by halide ions, mitigating one major instability issue of the perovskite devices. Here, the theory of bifacial PV devices is summarized and the advantages of bifacial perovskite solar cells, such as high power output, enhanced device durability, and low economic and environmental costs, are reviewed. The limitations and challenges for bifacial perovskite solar cells are also discussed. Finally, the awareness of bifacial solar cells as a feasible commercialization pathway of perovskite PV for mainstream solar power generation and building‐integrated PV is advocated and future research directions are suggested. Metal halide perovskites are an ideal candidate for fabricating bifacial thin‐film solar cells because of their outstanding optoelectronic properties and unique features of device physics. Bifacial perovskite solar cells hold the potential to simultaneously achieve higher energy yield and longer device stability than their monofacial equivalent, which provides a commercialization path for perovskite photovoltaics in the future.